2004
DOI: 10.1111/j.1440-1746.2003.03334.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in Saudi Arabia: Role of hepatitis B and C infection

Abstract: Hepatitis B virus constitutes a major risk factor and HCV contributes a less significant role in the development of HCC. The ongoing program of HBV vaccination may significantly decrease the prevalence of HBV-associated HCC in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…We observed that 60% of HCC patients were positive for anti‐HCV and 18% for HBsAg. By opposition, the HBsAg prevalence in HCC was lower than in Middle−Eastern countries, like Saudi Arabia and Lebanon . Thus, our data suggest that the low incidence of HCC in the region is may be linked to a weaker tumorigenic potential of circulating hepatitis viruses strains (genotype D7 vs. other D for HBV), to an absence of usual tumorigenic cofactors as aflatoxin B1 and also the life expectancy in each country.…”
Section: Hbv In Hepatocellular Carcinoma In the Maghrebmentioning
confidence: 60%
“…We observed that 60% of HCC patients were positive for anti‐HCV and 18% for HBsAg. By opposition, the HBsAg prevalence in HCC was lower than in Middle−Eastern countries, like Saudi Arabia and Lebanon . Thus, our data suggest that the low incidence of HCC in the region is may be linked to a weaker tumorigenic potential of circulating hepatitis viruses strains (genotype D7 vs. other D for HBV), to an absence of usual tumorigenic cofactors as aflatoxin B1 and also the life expectancy in each country.…”
Section: Hbv In Hepatocellular Carcinoma In the Maghrebmentioning
confidence: 60%
“…For example, Fakunle et al found 25% of their HCC patients to be anti-HCV positive and 45% positive for HBcAg (37). In the study by Ayoola and Gadour, it has been reported that HBV was more common than HCV in their population of HCC patients in the Jazan area (38). Saeed et al, also found more patients who were HBsAg positive than those who were anti-HCV positive (33.3% vs 26.2%) (39).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been published in the last two decades addressing various aspects of HBV infection in Saudi Arabia, such as its prevalence among the general population and the different age groups [1-5], blood donors [6,7], health care workers [8], pregnant women [9], virus genotypes and its relation to hepatocellular carcinoma [10,11]. These studies indicate that the disease is endemic in the kingdom and of major public health importance.…”
Section: Introductionmentioning
confidence: 99%